Clinical Relevance and Management of Recurrent Laryngeal Nerve Inlet Zone Lymph Nodes Metastasis in Papillary Thyroid Cancer - Zheng, Guibin; Wu, Guochang; Sun, Haiqing; Ma, Chi; Guo, Yawen; Wei, Dongmin; Yu, Wenbin; Zheng, Haitao; Song, Xicheng (Frontiers in Endocrinology, 2021)
Background: Recurrent nodal disease often occurs in recurrent laryngeal nerve inlet zone (RLNIZ), leading to difficult surgical manage. Methods: Medical records of 947 patients with PTC and 33 patients with recurrent PTC were retrospectively reviewed. Totally 169 sides of RLNIZ dissection in 152 patients (17 cases were bilateral and 135 cases were unilateral) with primary surgery and 4 patients with structural recurrent disease were included for the analysis. Results: The rate of lymph node metastasis in RLNIZ was 31.3% (47/150). The incidence of transient hypoparathyroidism was 5.9% and no RLN injury and permanent hypoparathyroidism occurred. RLNIZ lymph nodes metastasis (LNM) was significantly associated with age < 45 years, larger tumor size, number of CNLNM, and lateral nodes metastasis. CNLNM and Lateral nodes metastasis were independent risk factors for RLNIZ LNM. Recurrent nodal disease in RLNIZ was identified in 4 of 33 patients and permanent recurrent laryngeal nerve (RLN) injury was observed in 1 of 4 patients. Conclusion: Lymph nodes in RLNIZ are usually involved in patients with heavy tumor burden and can be removed safely at initial surgery. Once central or lateral LNM was confirmed preoperatively or intraoperatively, RLNIZ lymph nodes dissection should be carefully performed to reduce the rate of structural recurrence in the central compartment.